Analisis Laporan Realisasi Anggaran (LRA) dalam Menilai Kinerja Keuangan pada Kantor Camat Tanjung Pura Kabupaten Langkat - Raudhatul Jannah; Aqwa Naser Daulay (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The aim of this research is to help report users make decisions and show accountability for the use of resources. The Budget Realization Report offers information about financial conditions. The aim of this research is to evaluate the financial performance of the Tanjung Pura District Office using data from the 2019–2021 budget realization report. In public sector organizations, budgeting can help achieve accountability. The budget realization report shows the difference between the budget and its realization for a reporting period by providing an overview of the source, distribution and use of financial resources supervised by the local government. Efficacy and efficiency ratios are used in qualitative descriptive techniques. Interviews and scientific presentation of data, especially reports on regional income and expenditure budget achievements, were used to collect data from field research. Research findings show that the PAD revenue performance of 94.09% in 2019, 99.04% in 2020, and 100.7% in 2021 is effective. Likewise, the expenditure budget shows efficiency with a percentage of 78.91% in 2019, 63.79% in 2020, and 58.9% in 2021, all of which are in line with the goals to be achieved. To increase effectiveness and efficiency in the future, it is hoped that the Tanjung Pura District Office can continue to operate optimally, optimize the use of the budget wisely, and further review the benefits and budget allocations.